1985
DOI: 10.1266/jjg.60.455
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the glucose-6-phosphate dehydrogenase gene of Drosophila melanogaster using 17-base oligonucleotide mixtures as probes.

Abstract: Mixtures of 17-base long oligonucleotides possibly encoding a hexapeptide of Drosophila melanogaster glucose-6-phosphate dehydrogenase were synthesized and used as probes for screening a genomic library of D. melanogaster constructed in Charon 4A vectors. A total of about 60,000 plaques were initially screened, and after two successive plaque purification three clones carrying the identical 13-kb EcoRI fragment were isolated.That these clones contain the G6PD coding sequence was demonstrated by in situ hybridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
(10 reference statements)
1
7
0
Order By: Relevance
“…A recombinant EMBL3 library was constructed by ligating Sau3AI-digested genomic DNA into the BamHI site of the vector. 5) are summarized as follows: (1) the Insl consists of two defective P elements, each with the characteristic 31 bp inverted repeats as reported by O'Hare & Rubin (1983), (2) the sequence of the right P element perfectly matched that of the KP element reported by Black et al (1987) (the internal deletion ranged from base 808 to base 2560 and the 32nd base, adenine, was replaced by thymine), (3) the left P element also had the same nucleotide sequence as the KP element except for the 32nd base, guanine, (4) the orientation of the P elements was opposite to the G6PD gene (the direction of the G6PD transcription was previously reported by Hori et al 1985; it was recently confirmed by Ito et al who determined the initiation site of G6PD transcription by SI mapping and primer extension techniques, unpublished data), (5) the left and right P elements were flanked by duplicated target sequences of CTTGGGCG and CTGCGGCG, respectively, (6) there was a linking sequence, TTTGTTTG between the two defective P elements. Southern analysis of this clone showed that it carries two insertions; one was 2-3 kb long and located between the PvuII and the Pvu\ sites near the left end of exon I, and the other was 41 kb long and present between the Hin dill and the Eco RI sites within the intron (data not shown).…”
Section: Resultssupporting
confidence: 70%
“…A recombinant EMBL3 library was constructed by ligating Sau3AI-digested genomic DNA into the BamHI site of the vector. 5) are summarized as follows: (1) the Insl consists of two defective P elements, each with the characteristic 31 bp inverted repeats as reported by O'Hare & Rubin (1983), (2) the sequence of the right P element perfectly matched that of the KP element reported by Black et al (1987) (the internal deletion ranged from base 808 to base 2560 and the 32nd base, adenine, was replaced by thymine), (3) the left P element also had the same nucleotide sequence as the KP element except for the 32nd base, guanine, (4) the orientation of the P elements was opposite to the G6PD gene (the direction of the G6PD transcription was previously reported by Hori et al 1985; it was recently confirmed by Ito et al who determined the initiation site of G6PD transcription by SI mapping and primer extension techniques, unpublished data), (5) the left and right P elements were flanked by duplicated target sequences of CTTGGGCG and CTGCGGCG, respectively, (6) there was a linking sequence, TTTGTTTG between the two defective P elements. Southern analysis of this clone showed that it carries two insertions; one was 2-3 kb long and located between the PvuII and the Pvu\ sites near the left end of exon I, and the other was 41 kb long and present between the Hin dill and the Eco RI sites within the intron (data not shown).…”
Section: Resultssupporting
confidence: 70%
“…We find this particularly puzzling since the restriction map reported by Hori et al (1985) is identical to that previously published by Ganguly et al (1985). Although we have no explanation for this discrepancy, it seems likely that the data presented in Fig.…”
Section: (E) Nucleotide Homology Between Drosoplrilu and Human G6pd-cmentioning
confidence: 46%
“…Also, for this N terminus region of the human protein the amino acid sequence predicted by the cDNA M.G. Persico, personal communication) and the amino acid sequence obtained by direct protein sequencing (Takizawa et al, 1986) Hori et al (1985) have reported the cloning of the Drosophila Zw + gene utilizing oligodeoxynucleotide probes derived from the amino acid sequence of a hexapeptide of Drosophila melanogaster G6PD.…”
Section: (E) Nucleotide Homology Between Drosoplrilu and Human G6pd-cmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA and RNA were isolated from imagoes as described by Itoh et al (1988) and Hori et al (1985), respectively. Poly(A) + RNA was selected by oligo(dT)-cellulose chromatography as described by Aviv and Leder (1972).…”
Section: Preparation Of Dna and Rnamentioning
confidence: 99%